Injury prevention by surgical positioning: Integrative review (Research, Society and Development, 2024)
Surgical positioning promotes access to the surgical site; it must be carried out correctly, guaranteeing stability and safety for the patient, preventing complications. Objectives: analyze scientific productions on injury prevention through surgical positioning of adult patients intraoperatively; identify injuries resulting from failures and procedures used to prevent injuries resulting from surgical positioning. Methodology: integrative literature review study, prepared according to recommendations from the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guiding question: “what are the approaches to preventing injuries resulting from surgical positioning?” The inclusion criteria for the studies were: portraying the chosen theme; in portuguese, english and spanish; available for free and found with full text. The publication period covered january 2017 to july 2022. The expected exclusion criteria: incomplete text; articles not available for free; articles out of scope and not available for free. To select the articles, the BDENF, LILACS, MEDLINE and Scopus databases were used. Results: 13 studies selected, predominantly brazilian. Discussion: analysis categories: predictive scales, support surfaces, surgical position and affected regions; continuing education. Conclusion: predictive scales constitute a safe assessment practice, directing actions, scoring higher risk conditions. All surgical positions may pose some risk. The dry viscoelastic polymer mattress and viscoelastic cushions contribute to a low risk score on the elpo scale. Continuing education will be essential to maintain good practices, including the use of predictive scales.